2017
DOI: 10.1177/1049909117691280
|View full text |Cite
|
Sign up to set email alerts
|

Post-Acute Care Facility as a Discharge Destination for Patients in Need of Palliative Care in Brazil

Abstract: Patients with complex palliative care needs can experience delayed discharge, which causes an inappropriate occupancy of hospital beds. Post-acute care facilities (PACFs) have emerged as an alternative discharge destination for some of these patients. The aim of this study was to investigate the frequency of admissions and characteristics of palliative care patients discharged from hospitals to a PACF. We conducted a retrospective analysis of PACF admissions between 2014 and 2016 that were linked to hospital d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 32 publications
3
6
2
Order By: Relevance
“…In total, 3,015 patients were identified as having undergone a situation of bed blocking during the study period ( Pellico-López et al, 2019 ). In total, 198 (6.57%) of the 3,015 patients died during their prolonged stay, a result that is in line with other studies that specifically address the problem of death during prolonged stay ( Rosman et al, 2015 ), although another study found that one third of the patients who were waiting to be admitted in a post-acute care facility were palliative care patients ( Soares et al, 2018 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In total, 3,015 patients were identified as having undergone a situation of bed blocking during the study period ( Pellico-López et al, 2019 ). In total, 198 (6.57%) of the 3,015 patients died during their prolonged stay, a result that is in line with other studies that specifically address the problem of death during prolonged stay ( Rosman et al, 2015 ), although another study found that one third of the patients who were waiting to be admitted in a post-acute care facility were palliative care patients ( Soares et al, 2018 ).…”
Section: Discussionsupporting
confidence: 80%
“…In the literature there is evidence that situations of BB also arise in patients in need of palliative care ( Thomas & Ramcharam, 2010 ; Soares et al, 2018 ). The main users of hospital services are those suffering from chronic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Our study was one of the few to analyze ICU utilization during terminal hospitalizations and to analyze a PC intervention in a developing country. ( 32 , 33 ) Moreover, to our knowledge, this study is the first to demonstrate that a hospital PC program had an impact on outcomes in Brazil, even though it is a country in which it has been shown that quality of end-of-life care may be poor and PC of limited access. ( 34 ) Additionally, it has been suggested that there are differences between Brazil and other countries in things people seem to give importance to at the end of life, ( 35 ) such as the setting of death, ( 36 ) with Brazilians valuing more "living as long as possible" and being more likely to die in the hospital.…”
Section: Discussionmentioning
confidence: 76%
“…In the present study, the vast majority of patients with dementia had had a tube feeding and tracheostomy already in place at the time of palliative care referral. In Brazil, people with late stage dementia are often admitted to intensive care units to receive life sustaining treatments (7). In fact, the use of mechanical ventilation in hospitalized people with dementia has increased over the last decades (21).…”
Section: Discussionmentioning
confidence: 99%
“…Around the world, several palliative care programs are now serving people with dementia (6). In a recent study we found that advanced cancer and late stage dementia were the two most common underlying diagnosis among people admitted to a palliative care program in Brazil (7). Unfortunately, the organization and quality of palliative care services are usually better for cancer than for dementia (8).…”
Section: Introductionmentioning
confidence: 99%